Epithelial Cells Count and the Ratio of Leukocytes and Epithelial Cells as the Criteria to Determine Qualified Specimen for Community-Acquired Pneumonia (CAP)-causing Pathogens Identification - Ade Dharmawan; Anis Karuniawati; Pratiwi Pudjilestari Sudarmono; Delly Chipta Lestari; Cleopas Martin Rumende (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Community-acquired pneumonia (CAP) is the most common infectious with serious rate of morbidity and mortality. Recent conventional method only described 30-50% of CAP etiology. Sputum specimen quality assessment is important to obtain an accessible CAP-causing pathogens identification.METHODS: This was a prospective descriptive study involving 100 specimens from CAP-diagnosed subjects in Budhi Asih Regional General Hospital inpatien tcare. We assessed three gram-staining criteria for specimen quality determination, and continued by bacterial identification.RESULTS: All specimens were qualified according to criteria II, while only 94 and 96 specimens were qualified according to criteria I and III, respectively. Sixty-five specimens could be identified by culture and pneumoCLART polymerase chain reaction (PCR) examination, and the 35 specimens remained unknown. Ten out of those 35 specimens were positive after analyzed by Acid-fast Bacilli (AFB) test. The pathogens we identified including Klebsiella pneumoniae (29.6%), Acinetobacter baumanii (10.2%), Enterobacter cloacae (4.6%), Pseudomonas aeruginosa (4.6%), Staphyloccocus aureus (4.6%), Moraxella catarrhalis (3.7%), Enterobacter aerogenes (2.8%), Escherichia coli (2.8%), Streptococcus pneumoniae (1.9%), Mycoplasma pneumoniae (1.9%) and Citrobacter koseri (0.9%).CONCLUSION: There were no significant differences among the three criteria for sputum specimen quality assessment, based on culture and pneumoCLART examination. We suggest that criteria II could be used to avoid many specimen rejections while good quality specimens still attained for accessible bacteria identification.KEYWORDS: community-acquired pneumonia, sputum, gram stain, pathogens, bacteria